Evidence of oblique electron acoustic solitary waves triggered by magnetic reconnection in Earth's magnetosphere. (1st January 2023) - Atteya, A; EL-Labany, S K; Karmakar, P K; Afify, M S
Abstract: Motivated by the recent Magnetospheric Multiscale (MMS) observations of oblique electron acoustic waves, we addressed the generation mechanism of the observed waves by utilizing the reductive perturbation technique. A nonlinear Zakharov-Kuznetsov (ZK) equation is derived for a collisionless, magnetised plasma composed of cool inertial background electrons, cool inertial electron beam, hot inertialess suprathermal electrons; represented by a κ -distribution, and stationary ions. Moreover, the instability growth rate is derived by using the small- k perturbation expansion method. Our findings revealed that the structure of the electrostatic wave profile is significantly influenced by the external magnetic field, the unperturbed hot, cool, and electron beam densities, the obliquity angle, and the rate of superthermality. Such parameters also have an effect on the instability growth rate. This study clarifies the characteristics of the oblique electron solitary waves that may be responsible for changing the electron and ion distribution functions, which alter the magnetic reconnection process. Moreover, the increase of the growth rate with the plasma parameters could be a source of anomalous resistivity that enhances the rate of magnetic reconnection.